2019
DOI: 10.1108/emjb-06-2019-0079
|View full text |Cite
|
Sign up to set email alerts
|

Factors that impact farmers’ engagement in local food brand development

Abstract: Purpose The purpose of this paper is to explore farmers’ intentions to engage in food brand development schemes and identify the factors that impact this. Design/methodology/approach By assuming the utility maximization behavior of farmers, based on data collected from 539 fruit and vegetable producers, this study estimates an intention to participate and a willingness to pay model. Findings Three groups of factors determine the utility the farmers derive and subsequently their engagement in brand developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Among the variables of the model, the brand has been included as a preferred food quality attribute. This finding, along with prior studies on food brand as a quality indicator in farming (Tselempis et al. , 2020), opens avenues of integrated research along the food value chain.…”
Section: Discussionsupporting
confidence: 61%
“…Among the variables of the model, the brand has been included as a preferred food quality attribute. This finding, along with prior studies on food brand as a quality indicator in farming (Tselempis et al. , 2020), opens avenues of integrated research along the food value chain.…”
Section: Discussionsupporting
confidence: 61%
“…Low satisfaction with retail also triggered farmers to adopt direct sales in a case study in Greece (Tselempis et al 2020), potentially reflecting a similar process. Tselempis et al (2020) also highlighted how interaction between consumers and farmers triggered farmers who perceived consumer interest in local food to start direct sales. This interaction particularly takes place at easily accessible locations (Fig.…”
Section: Enabling Factors For Sustainable Intensificationmentioning
confidence: 97%
“…Recent research showed that this sentiment is shared by many Dutch farmers, as the competition for consumers by supermarkets and other market parties in the food chain gives a continuous pressure on prices, also in the agricultural chains (Baltussen et al 2018). Low satisfaction with retail also triggered farmers to adopt direct sales in a case study in Greece (Tselempis et al 2020), potentially reflecting a similar process. Tselempis et al (2020) also highlighted how interaction between consumers and farmers triggered farmers who perceived consumer interest in local food to start direct sales.…”
Section: Enabling Factors For Sustainable Intensificationmentioning
confidence: 99%
“…The literature analysis proposed here shows that the concept of COO has undergone significant changes due to the different approaches adopted, the globalization process and the variables considered (Rosado-Pinto and Louriero, 2020). However, what seems to have never changed is how the COO effect is considered, which is a variable affecting consumer behavior and supporting competitive challenges, particularly those of choosing the product and brand abroad (Amatulli et al, 2019;Tselempis et al, 2019). Pongjit and Chiaravutthi (2018) argued that intangible resources, such as the COO effect, are often harder to imitate, have more uses and can be more easily redeployed after a change than tangible resources.…”
Section: Ijebr 285mentioning
confidence: 99%